2013
DOI: 10.1021/jp311852j
|View full text |Cite
|
Sign up to set email alerts
|

Size Control to a Sub-Nanometer Scale in Platinum Catalysts on Graphene

Abstract: Size controlled Pt catalysts supported by graphene nanosheets (GNS) are successfully prepared by changing the loading of Pt at 10−70 wt % using an impregnation method. It is found that Pt sub-nanoclusters (0.8 nm) with an extremely large surface area (170 m 2 g −1 ) are formed on the GNS support in a 10 wt % Pt/GNS catalyst. An increase in loading of Pt leads to an increase in the particle sizes of Pt, which results in lower activities for electrooxidation of adsorbed CO. A core level shift of Pt 4f in XPS ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 31 publications
(84 reference statements)
3
67
0
Order By: Relevance
“…4c. A similar shift of the Pt 4f peak towards a higher binding energy was also reported for small Pt clusters and this upshift has been attributed to the increase in the number of Pt atoms with low coordination numbers223334.…”
supporting
confidence: 78%
“…4c. A similar shift of the Pt 4f peak towards a higher binding energy was also reported for small Pt clusters and this upshift has been attributed to the increase in the number of Pt atoms with low coordination numbers223334.…”
supporting
confidence: 78%
“…For example, due to its high surface area and low manufacturing cost, graphene has been used as substrate for surface-supported catalysis. Graphene-supported nanocatalysis with Pt [150][151][152][153], Pd [154], Au [155,156], and metal alloys [157][158][159][160][161][162] has been reported. The thermal stability of transition and noble metal nanostructures on graphene is crucial for the performance of the catalysis applications.…”
Section: Thermal Stability Of Metal Nanoclustersmentioning
confidence: 99%
“…9. It is shown that the main peaks related to Pd 0 do not change significantly after adsorption on support material, and noticed that the peak position can be influenced from different parameters such as support material (due to electronic interactions) and nanoparticle size [55][56][57]. Takasu et al reported a shift to lower binding energies when the particle size of Palladium nanoparticles deposited on SiO 2 was increased [58].…”
Section: Catalyst Fabrication By Adsorption Of Palladium Nanoparticlementioning
confidence: 99%